2007
DOI: 10.1097/01.imi.0000250499.99341.97
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Off-Pump Reoperative Coronary Artery Bypass Grafting

Abstract: Objective Application of off-pump techniques to reoperative coronary artery bypass (redo CABG) has been limited by technical difficulty and potential for embolism of atheromatous debris from diseased grafts, resulting in myocardial infarction and rapid hemodynamic deterioration. We compared outcomes after off-pump (OPCAB) and on-pump (ONCAB) in redo CABG. Methods A retrospective chart review was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…In a propensity-matched comparison of reoperative OPCAB versus ONCAB, Morris et al [31] reported a significant reduction in overall postoperative complications, atrial fibrillation, blood transfusion, and hospital LOS. Mishra et al similarly demonstrated a reduction in need for prolonged ventilator and inotropic support, and shorter ICU and hospital LOS in favor of redo OPCAB [32].…”
Section: Reoperative Coronary Artery Bypass Graftingmentioning
confidence: 97%
“…In a propensity-matched comparison of reoperative OPCAB versus ONCAB, Morris et al [31] reported a significant reduction in overall postoperative complications, atrial fibrillation, blood transfusion, and hospital LOS. Mishra et al similarly demonstrated a reduction in need for prolonged ventilator and inotropic support, and shorter ICU and hospital LOS in favor of redo OPCAB [32].…”
Section: Reoperative Coronary Artery Bypass Graftingmentioning
confidence: 97%
“…The incidence of post-operative atrial fibrillation was 5.05% in the OPCAB group and 13.8% in the ONCAB group, as reported by seven studies [10,12,14,16,17,20,21]. This reduction with OPCAB was statistically significant using the random effects model (OR 0.41; 95% CI 0.22-0.77) (Figure 7), without significant heterogeneity between the studies.…”
Section: Resultsmentioning
confidence: 58%
“…Of the 12 studies, five used cold blood cardioplegia [12,14-16,21], one used cold crystalloid [10], 2 used a combination of cold blood and cold crystalloid [11,20] and one study used a combination of cold blood, warm blood and hypothermic ventricular fibrillation [19]. The majority of studies (5/9) administered a combination of antegrade and retrograde cardioplegia [11,14,16,17,21]. Two studies used only an antegrade approach [19,20] and the remainder did not specify their technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Shroff and colleagues [24 ] reported only a modestly increased survival advantage for OPCAB patients. In patients with left-ventricular dysfunction [25,26], previous sternotomy [27], advanced age [27][28][29][30], previous stroke [31], and in female patients [32], more favorable outcomes have been reported with OPCAB compared with ONCAB. Emmert and associates [33 ] reported excellent outcomes in patients with left main disease undergoing OPCAB.…”
Section: High-risk Patientsmentioning
confidence: 94%